Zapisz w jak najprostszej postaci :

(2a + b) * c - (2a + b) * d = .................................
5(x - z) + a(z - x) = .....................
2x ''do potegi 2'' (x - 5) - 3x(x ''do potęgi 2'' - 3x + 5) = ....................
6(a ''do potęgi 2'' + 1/2b + 1/3c) - 6(a ''do potęgi 2'' - 1/2) - 3(b ''do potęgi 2'' + 1/3) = .................................

1/2 i 1/3 - UŁAMKI !!!

2

Odpowiedzi

2009-12-11T18:29:33+01:00
(2a + b) * c - (2a + b) * d = 2ab*c-2ab*c=2abc-2abc

5(x - z) + a(z - x) =5x-5z+az-ax

2x ''do potegi 2'' (x - 5) - 3x(x ''do potęgi 2'' - 3x + 5) = 4x*x-5-3x*x-3x+5

6(a ''do potęgi 2'' + 1/2b + 1/3c) - 6(a ''do potęgi 2'' - 1/2) - 3(b ''do potęgi 2'' + 1/3) = 6*a+½+⅓c-6*a-½
2009-12-11T18:41:58+01:00
(2a+b)*c-(2a+b)*d=2ac+bc-2ad-bd

5(x-z)+a(z-x)=5x-5z+az-ax

2x"do potegi 2"(x-5)-3x(x"do potegi 2"-3x+5)=2x"do potegi3"-10-3x"do potegi 3"+9x"do potegi 2"-15x=-x"do potegi3"-10+9x"do potegi 2"-15x

6(a ''do potęgi 2'' + 1/2b + 1/3c) - 6(a ''do potęgi 2'' - 1/2) - 3(b ''do potęgi 2'' + 1/3) = 6a"do potegi 2"+3b+2c-6a"do potegi 2"+3-3b"do potegi 2"-1=3b+2c-3b"do potegi 2"-2